Synthesis, Characterization, and Toxicity Assessment of Zinc Oxide-Doped Manganese Oxide Nanoparticles in a Macrophage Model - Nasser B. Alsaleh; Anas M. Aljarbou; Mohamed E. Assal; Mohammed A. Assiri; Mohammed M. Almutairi; Homood M. As Sobeai; Ali A. Alshamrani; Sultan Almudimeegh; Mohammad R. Hatshan; Syed F. Adil (MDPI AG, 2024)
The doping of engineered nanomaterials (ENMs) is a key tool for manipulating the properties of ENMs (e.g., electromagnetic, optical, etc.) for different therapeutic applications. However, adverse health outcomes and the cellular biointeraction of doped ENMs, compared to undoped counterparts, are not fully understood. Previously, we have shown that doping manganese oxide nanoparticles with ZnO (ZnO-MnO2 NPs) improved their catalytic properties. In this study, we assessed the toxicity of ZnO-MnO2 NPs in Raw 264.7 cells. NPs were prepared via an eco-friendly, co-precipitation method and characterized by several techniques, including transmission and scanning electron microscopy, X-ray diffraction, and Fourier transform infrared. The physicochemical properties of ZnO-MnO2 NPs, including size, morphology, and crystalline structure, were almost identical to MnO2 NPs. However, ZnO-MnO2 NPs showed slightly larger particle aggregates and negative charge in cell culture media. Exposure to ZnO-MnO2 NPs resulted in lower toxicity based on the cell viability and functional assay (phagocytosis) data. Exposure to both NPs resulted in the activation of the cell inflammatory response and the generation of reactive oxygen species (ROS). Despite this, exposure to ZnO-MnO2 NPs was associated with a lower toxicity profile, and it resulted in a higher ROS burst and the activation of the cell antioxidant system, hence indicating that MnO2 NP-induced toxicity is potentially mediated via other ROS-independent pathways. Furthermore, the cellular internalization of ZnO-MnO2 NPs was lower compared to MnO2 NPs, and this could explain the lower extent of toxicity of ZnO-MnO2 NPs and suggests Zn-driven ROS generation. Together, the findings of this report suggest that ZnO (1%) doping impacts cellular biointeraction and the consequent toxicological outcomes of MnO2 NPs in Raw 264.7 cells.